DETERMINANT IN GENERATION Z'S SHARIA TOURISM DECISIONS: THE ROLE OF DIGITALIZATION - Nafi’ah, Uswatun; Warsitasari, Wahyu Dwi; Muna, Natasya Lailiya Khoril; Chotimah, Chusnul; Muniri, Muniri (Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2025)
Abstract: The growth of digital technology has resulted in huge changes in many aspects of life, including the tourist industry. This study seeks to analyse the influence of digitalisation, as assessed by two independent variables, namely digital literacy and the use of digital material, on Islamic tourism decisions among Generation Z in East Java. This study employs a quantitative method with a population of Generation Z in East Java. The sample approach used was accidental sampling, with 402 respondents chosen using the Slovin formula. Primary data was collected using a questionnaire designed to measure digital literacy, digital content consumption, and sharia tourism choices. The SEM-PLS model was used to examine data to assess the degree to which digital literacy and digital content utilisation impact Generation Z's decision to visit Sharia, both directly and indirectly.This study's findings indicate that digital literacy and the consumption of digital material both have a significant influence on the decision to visit Sharia Tourism Generation Z in East Java. Experience with digital material for tourism can mitigate the impact of varying tourism digital literacy on Sharia tourist decisions. The findings of this study are likely to help Sharia tourism industry operators optimise digitalisation efforts in order to improve Generation Z interest in and decision-making regarding Sharia tourism. Keywords: generation z; sharia tourism decisions; digitalization. Abstrak: Pertumbuhan teknologi digital telah menyebabkan perubahan besar dalam banyak aspek kehidupan, termasuk industri pariwisata. Penelitian ini bertujuan untuk menganalisis pengaruh digitalisasi, yang dinilai dari dua variabel independen, yaitu literasi digital dan penggunaan materi digital, terhadap keputusan pariwisata Islam di kalangan Generasi Z di Jawa Timur. Penelitian ini menggunakan metode kuantitatif dengan populasi Generasi Z di Jawa Timur. Pendekatan sampel yang digunakan adalah sampling aksidental, dengan 402 responden yang dipilih menggunakan rumus Slovin. Data primer dikumpulkan menggunakan kuesioner yang dirancang untuk mengukur literasi digital, konsumsi konten digital, dan pilihan pariwisata syariah. Model SEM-PLS digunakan untuk menganalisis data guna menilai sejauh mana literasi digital dan pemanfaatan konten digital mempengaruhi keputusan Generasi Z untuk mengunjungi Pariwisata Syariah, baik secara langsung maupun tidak langsung. Hasil penelitian ini menunjukkan bahwa literasi digital dan konsumsi materi digital memiliki pengaruh yang signifikan terhadap keputusan untuk mengunjungi Pariwisata Syariah oleh Generasi Z di Jawa Timur. Pengalaman dengan materi digital untuk pariwisata dapat membantu mengurangi dampak perbedaan literasi digital pariwisata terhadap keputusan pariwisata syariah. Temuan dari penelitian ini dapat membantu operator industri pariwisata syariah untuk mengoptimalkan upaya digitalisasi guna meningkatkan minat dan pengambilan keputusan Generasi Z terkait pariwisata syariah. Kata Kunci: generasi z; keputusan berwisata syariah; digitalisasi.